CHRISTIANITY AS THE CRADLE OF MODERN SCIENCE AND ITS INFLUENCES ON SCIENTIFIC RESEARCH - Damião da Silva Rodrigues, Cicero; da Silva Lacerda Júnior, Orivaldo (Revista Gênero e Interdisciplinaridade, 2022)
The condemnation of Galileo Galilei, a milestone in the history of science, is interpreted as if the Catholic Church were an oppressive institution and against scientific investigation. However, much of what we are taught is nothing more than myth or legend, such as persecution and condemnation at the bonfire. In fact, far from persecuting him, the Roman Catholic Apostolic Church welcomed Galileo as a son and, moreover, it was the cradle of science and the university system, for being the institution that was most interested in cultivating knowledge, it was also the one that invested most in astronomy. Previously called natural philosophy, modern science was influenced by the priests of the Catholic Church, mainly by the Jesuits who were pioneers in astronomy. Priests like Nicolaus Copernicus, who started the theory of heliocentrism, Roger Boscovich, a Jesuit priest who gave the first coherent description of the atom giving rise to the first modern atomic theories, Gregor Mendel, who was the monk who performed experiments with peas, Georges Lemaître, the Belgian priest who created the Big Bang theory. These and many others made great discoveries that made science take great leaps. Not discarding other civilizations and religions, pantheists, who brought a lot of wisdom, such as the Incas, Mayans, Babylonians, Egyptians, etc., but the Christian Church was the only one that reached to take science to another level, for it was based on the belief of a single God who had created all things with physical order and laws. Therefore, the objective of this work is to contest the idea that the Church is opposed to Science, exposing the difference between the two and aiming at scientific investigations carried out by priests. Concluding that this Christian institution did not persecute science, but made great leaps, did not burn scientists on the bonfire because of their ideas, did not delay science in the medieval and the conflict or divergence is the result of criticism made for the Church by Enlightenment thinkers and the story badly told full of fantasies.